Nitrogen use efficiency—a key to enhance crop productivity under a changing climate - Govindasamy, Prabhu; Muthusamy, Senthilkumar K.; Bagavathiannan, Muthukumar; Mowrer, Jake; Jagannadham, Prasanth Tej Kumar; Maity, Aniruddha; Halli, Hanamant M.; G. K., Sujayananad; Vadivel, Rajagopal; T. K., Das; Raj, Rishi; Pooniya, Vijay; et al. (Frontiers in plant science, 2023)
Nitrogen (N) is an essential element required for the growth and development of all plants. On a global scale, N is agriculture’s most widely used fertilizer nutrient. Studies have shown that crops use only 50% of the applied N effectively, while the rest is lost through various pathways to the surrounding environment. Furthermore, lost N negatively impacts the farmer’s return on investment and pollutes the water, soil, and air. Therefore, enhancing nitrogen use efficiency (NUE) is critical in crop improvement programs and agronomic management systems. The major processes responsible for low N use are the volatilization, surface runoff, leaching, and denitrification of N. Improving NUE through agronomic management practices and high-throughput technologies would reduce the need for intensive N application and minimize the negative impact of N on the environment. The harmonization of agronomic, genetic, and biotechnological tools will improve the efficiency of N assimilation in crops and align agricultural systems with global needs to protect environmental functions and resources. Therefore, this review summarizes the literature on nitrogen loss, factors affecting NUE, and agronomic and genetic approaches for improving NUE in various crops and proposes a pathway to bring together agronomic and environmental needs.